Drug management of oxidation-reduction state of the body in respiratory tract diseases (part 5) - A.E. Abaturov; A.P. Volosovets; T.P. Borysova (Zaslavsky O.Yu., 2018)
The review of the literature presents modern data on antioxidant activity and immunomodulatory action of vitamin A in diseases of the respiratory system.